Analysis of Leakage Current and Insulator Resistivity for Quality Assurance of Medium Voltage Network Polymer Insulators Alumina - SiO2 in Tropical Climate Simulator Room - Agnes Manik Sari Utami; Abdul Syakur; Hermawan Hermawan (TEKNIK, 2021)
The tropical climate of Indonesia, which has moderately high rainfall, has an impact on the output of outdoor insulators. The presence of chemical particles, pollen, and salt in the air will bind to the insulating material's outer surface and settle, resulting in crystallization that allows the insulating material's surface roughness to increase. One of the insulators that are being produced is an insulator made of epoxy resin. The injection of fillers is used to further improve the durability of the outdoor epoxy resin insulators installed in tropical climatic conditions. Epoxy resin from bisphenol A-epichlorohydrin and polyaminoamide combined with silane, alumina, and SiO2 is used as research materials. The parameters examined were leakage current and resistance to insulation. The use of silane as a hardener will also improve the resistivity on the surface of the insulator, which makes it more difficult to flow or reduces the leakage current. Alumina is well-known for being a solid heat and voltage insulator. The addition of SiO2 to the epoxy resin insulating material increases the insulator's mechanical strength in the form of tensile and compressive strength. With fluctuations in temperature and humidity, the artificial tropical environment is replicated in a test chamber. The value of the leakage current increases with an increase in temperature and humidity. The correlation between air temperature and humidity and insulation resistance is inversely proportional, the higher the temperature applied to the insulator, the lower the insulator resistivity. The same refers to the relationship between air humidity and resistance to insulation. The higher the humidity applied to the insulator, the lower the insulator resistivity. At a test voltage of 11 kV, a humidity of 60%, and a temperature variation of 25oC, the leakage current of epoxy resin insulators is up to 9.2 uA lower than in a factory-made SiR insulator. The leakage current and insulator resistivity's number is already in the good and protected range such that the insulator can be used and reproduce.